Pengaruh Model Pembelajaran Generatif Dengan Metode PQ4R Melalui Scaffolding Terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik - Sri Maryani; Hairunnisyah Sahidu; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
Student often found that physics full of difficulty by using many equations to solve some problems and this lead to the decreased of problem solving ability in physics. One of the ways that suggested to increase problem solving in physics is using generative learning combined with PQ4R method and scaffolding. Because of that, this research aim to discover the influence of generative learning with PQ4R method through scaffolding toward ability to solve problem in physics. The type of this study is quasi experimental with non-equivalent control grup design with pretest-postest. Sampling was done by purposive sampling technique with XI MIA 2 as the experimental class and XI MIA 3 as the control class. The experimental class in this study was given generative learning with PQ4R method and scaffolding, while the control class was given conventional learning as the treatment. The results of ability to solve problem was obtained by essay test which consist 7 items and analyzed using t-test polled varians. Data analysis show that Ho was refused and the Ha was accepted. Therefore, there was an effect of generative learning with PQ4R method through scaffolding toward problem solving in physics.